First lactation production traits of Frieswal cows under field conditions - Sanjay Kumar and Anil Kumar, S.K. Minj, D.V. Singh C.B. Singh, Shiv Prasad (Indian Journal of Animal Production and Management, 2019)
The Frieswal (HFxSahiwal crossbred) cows are important for milk production in India. An investigationwas carried out with farmers of U.S.Nagar district of Uttarakhand on Frieswal cows (Nov. 2010 to Feb.2016) to study the effect of various non-genetic factors (blocks, herd size, land holding, education level offarmers, caretakers of herd, marketable milk surplus, season/ year of calving) on first lactation productiontraits using least-squares analysis of variance. The overall values for lactation length and 305-days milkyield based on 220 observations were 11.32±0.65 kg, 342.97±12.14 days, 2434.72±187.12 kg; and ofmonthly fat test for 2nd, 5th and 8th month and overall fat test based on 236 observations were 3.447±0.073,3.735±0.075, 3.908±0.075 and 3.694±0.061 per cent, respectively. These traits were significantly affectedby varying non-genetic factors. Information on this aspect may be useful while implementing field basedanimal breeding program of crossbred cattle.